2013
DOI: 10.1519/jsc.0b013e318269f7f1
|View full text |Cite
|
Sign up to set email alerts
|

The Validity of the SmartJump Contact Mat

Abstract: The aim of this study was to establish the criterion validity of the SmartJump contact mat in assessing vertical jump height (VJH) and peak power (PP). Twenty-three participants (15 men, age = 26 ± 6 years; 8 women, age = 26 ± 9 years) completed a maximal effort vertical jump using 3 different jump types (countermovement jump [CMJ], countermovement with arms [CMJA], and squat jump [SJ]). Data were simultaneously collected on both the contact mat and force platform. Vertical jump height was calculated using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 16 publications
3
20
0
Order By: Relevance
“…The influence of the computational approach implemented on the vertical height computed from SJs and CMJs has been reported elsewhere (9,25,36), confirming that the specific determination of jump test variables relies on the computational method chosen and limits the absolute comparability of published material using different methodologies.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…The influence of the computational approach implemented on the vertical height computed from SJs and CMJs has been reported elsewhere (9,25,36), confirming that the specific determination of jump test variables relies on the computational method chosen and limits the absolute comparability of published material using different methodologies.…”
Section: Resultsmentioning
confidence: 67%
“…Although jump test parameters derived from GRFs are often used as a "gold-standard" or reference criterion (8,16,36), extracting parameters from force-plates also has its limitations. In particular, the data manipulation required to extract the performance variables amplifies any noise in the raw signal (46), which increases the risk of accumulating error in results (12).…”
Section: Resultsmentioning
confidence: 99%
“…Jump height was calculated from take-off velocity (take-off velocity 2 ÷ 2g) (20). Velocity was obtained by integrating acceleration with respect to time using the trapezoid rule using the method described by Owen et al (18) Acceleration was obtained by dividing force (less weight…”
Section: Discussionmentioning
confidence: 99%
“…However, the results of this study showed that there was a small but significant difference between the propulsion (240.49 ± 24.46 Ns) and landing (250.77 ± 35.94 Ns) impulses. It is likely that this is a consequence of the differences between take-off and landing position that have been posited to cause differences between jump heights obtained from flight time and take-off velocity (8,20). This reinforces the need for practitioners to exercise caution when choosing a method to obtain loaded vertical jump height because these differences could have a direct impact on the accuracy of vertical jump heights…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…In order to control the arm countermovement between trials, participants were asked to maintain their hands at waist level throughout the jumping maneuver. Jump performance was quantified by the maximum jump height and the peak jump power, measured by a validated tool Smartjump™ (Fusion Sport, Queensland, Australia) according to the previously documented method (Reeve and Tyler, 2013). Mean values of the outcome variables were averaged between three attempts.…”
Section: Testing Proceduresmentioning
confidence: 99%